One-pot sequential bromination and fluorination to access 3-fluoroimidazo[1,2-a]pyridines from arylketones - Udavant, R. N.; Yadav, A. R.; Shinde, S. S. (European Journal Of Organic Chemistry, 2018)
3-Fluoro-2-arylimidazo[1,2-a]pyridines were selectively synthesised in one-pot from acetophenones and 2-aminopyridines under mild conditions. The sequence of reactions involved bromination, condensation, and late-stage fluorination. Two halogenating reagents play key roles in the process. We found that tetrabutylammonium tribromide and SelectfluorTM gave excellent yields of the desired products in the one-pot sequential reaction. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim